Bentuk Emosi Tokoh dalam Novel Hold On, It Hurts: Kajian Psikologi Sastra Paul Ekman: The Expression of Characters’ Emotions in the Novel ‘Hold On, It Hurts’: A Literary Psychology Study by Paul Ekman - Marpaung, Grace; Harahap, Nurhayati; Marsella, Emma (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to describe the emotional expressions of the main character, Anindia, in Noveni Adelia’s novel ‘Hold On, It Hurts’ through the perspective of literary psychology. The focus of this study is to identify the emotional manifestations of Anindia, who is experiencing complex domestic conflicts. The research method used is descriptive qualitative. The primary data source for this study is the novel ‘Hold On, It Hurts’ by Noveni Adelia. Data were collected using the read-and-record technique, involving repeated reading, noting quotations, and classifying them based on theory. Data analysis was conducted descriptively using Paul Ekman’s theory of the six basic emotions: sadness, anger, surprise, fear, disgust, and happiness. The results of the study indicate that the character Anindia experiences all six of these emotions, triggered by her husband’s (Jeandra) betrayal, the presence of a third party (Karinina), domestic violence, and the loss of her professional identity as a doctor due to slander. Sadness and anger emerge as the most dominant emotions in response to the collapse of her marital hopes and the injustices she faces. This study concludes that the depiction of emotions in the novel accurately reflects the psychological turmoil humans face when dealing with trauma and severe mental stress.